Pathophysiology and potential treatment modalities in women with recurrent urinary tract infection - Wei-Ju Liao; Yuan-Hong Jiang; Jia-Fong Jhang; Sheng-Fu Chen; Yu Khun Lee; Cheng-Ling Lee; Tien-Lin Chang; Hann-Chorng Kuo (Tzu Chi Medical Journal)
Urinary tract infection (UTI) of the urinary bladder is a common bacterial infection that predominantly affects women, with many experiencing recurrent episodes. Recurrent UTIs (rUTIs) are associated with significant physical, psychological, and social difficulties. Further, they are closely related to lower urinary tract dysfunction (LUTD). LUTD affects bladder function and structure, thereby contributing to urinary urgency, frequency, and incontinence, which, in turn, increases the risk of recurrent infections due to impaired urothelial defense mechanisms. The current study explored the pathophysiology of LUTD in women with rUTIs. Potential treatments for rUTIs include long-term prophylactic antibiotics, probiotics, D-mannose, vaccines, small molecule inhibitors, and stem cell therapy. Moreover, it evaluated the use of platelet-rich plasma (PRP) therapy as a treatment modality for LUTD. PRP has regenerative and anti-inflammatory properties. Hence, it can be a promising option for enhancing urothelial barrier integrity and reducing infection recurrence. Repeated intravesical PRP injections are effective in improving bladder symptoms and decreasing UTI recurrences by enhancing the proliferative ability of the urothelium in patients with rUTIs. Further, this review examined the potential predictors of successful PRP treatment outcomes such as cytokine and urothelial biomarker levels, which provided insights into patient selection and individualized treatment strategies. Identifying the predictive biomarkers of treatment responsiveness is essential for optimizing PRP therapy. Hence, to improve the clinical outcomes and quality of life of patients with rUTIs, future research should focus on refining the use of PRP, exploring combination therapies, and validating biomarkers.